BENTUK DAN POLA SEBARAN TINGGALAN BUDAYA MEGALITIK DI KABUPATEN BIMA, PROVINSI NUSA TENGGARA BARAT - Heri, Heri Nopiyanto; Akin Duli; Erni Erawati; Khadijah Tahir Muda (JURNAL ILMU BUDAYA, 2024)
The purpose of this study was to analyze the form and distribution pattern of megalithic cultural relics found in Bima Regency. The method used is a survey to see the entire site to obtain data on the shape and type of megalithic culture. In general, the results of this study show that there are six sites, namely Wadu Ntari Site, Wadu Nocu So Kaliwu Site, Wadu Nocu So Jalamba Site, Wadu Nocu Site, Wadu Nocu Renda Site, and Wadu Nocu Laraji Site. In total, there are 17 remains, namely wadu nocu (15 finds), wadu dako (one find), and wadu lesu (one find). Most of the sites are scattered in a random pattern, where the sites occupy plantation land, close to human settlements and rivers. Based on their environmental conditions, the sites are scattered in mountainous and lowland areas with altitudes between 60-720 meters above sea level.